Left hand of darkness - Ursula K. Le Guin; GUIN (Ursula K. Le) (London Orion Publishing Group Ltd, 2017)
Genly Ai is an ethnologist observing the people of the planet Gethen, a world perpetually in winter. The people there are androgynous, normally neuter, but they can become male or female at the peak of their sexual cycle. They seem to Genly Ai alien, unsophisticated and confusing. But he is drawn into the complex politics of the planet and, during a long, tortuous journey across the ice with a politician who has fallen from favour and has been outcast, he loses his professional detachment and reaches a painful understanding of the true nature of Gethenians and, in a moving and memorable sequence, even finds love$1! =s
winner of the Hugo and Nebula Awards for Best Novel
Keywords: Science Fiction